2005
DOI: 10.1200/jco.2004.00.5355
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity in Children Receiving Platinum Chemotherapy: Underestimating a Commonly Occurring Toxicity That May Influence Academic and Social Development

Abstract: Traditional reporting of toxicity data (CTCAE) has under-reported ototoxicity and minimized the significance of hearing loss in children. As pediatric patients experience improved survival, the effects and implications of high-frequency hearing loss with regard to academic achievement and speech and language development are important considerations, especially in patients younger than 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
384
2
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(408 citation statements)
references
References 26 publications
10
384
2
12
Order By: Relevance
“…Previous studies have revealed hearing impairments mainly in patients <5 years old (20,24,25). In the adult group, hearing impairments were identified in 6/17 (35.3%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed hearing impairments mainly in patients <5 years old (20,24,25). In the adult group, hearing impairments were identified in 6/17 (35.3%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin causes significant permanent hearing loss in 20-80 % of treated patients (Fausti et al 1994;Knight et al 2005;Coradini et al 2007;Lewis et al 2009, reviewed in Neuwelt andBrock 2010). Risk factors that increase the likelihood of cisplatin-induced hearing loss include patient age, gender, cumulative cisplatin dose, certain genetic alleles, and radiation to the base of the skull (Schaefer et al 1985;Schell et al 1989;Li et al 2004;Huang et al 2007;Caronia et al 2009;Ross et al 2009;Yancey et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Rybak (2005), hearing loss occurs in 30 to 100% of patients treated with cisplatin. Hearing loss may occur during treatment (Knight et al, 2005(Knight et al, , 2007Orgel et al, 2012) or after discontinuation of chemotherapy (Al-Khatib et al, 2010;Kolinsky et al, 2010). Furthermore, patients treated with cisplatin exhibit severe difficulty in word recognition (Einarsson et al, 2011), suggesting a central component in their hearing loss.…”
Section: Introductionmentioning
confidence: 99%